2018
DOI: 10.3171/2018.3.peds1825
|View full text |Cite
|
Sign up to set email alerts
|

Acute fatal hemorrhage from previously undiagnosed cerebral arteriovenous malformations in children: a single-center experience

Abstract: OBJECTIVEThe most significant adverse outcome of intracranial hemorrhage from an arteriovenous malformation (AVM) is death. This study reviews a single-center experience with pediatric AVMs to quantify the incidence and characterize clinical and radiographic factors associated with sudden death from the hemorrhage of previously undiagnosed AVMs in children.METHODSA single-center database review of the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
1
4
1
1
Order By: Relevance
“…The mortality in the adult population is similar to that reported by Hillman, et al 26 as well as other literature, such as Rinaldi et al 21 who reported 13.46% mortality rate and other studies with a range from 10 to 15%. 17,20 However, the mortality in the pediatric population is vastly different from that of the literature, being 33.3% in our study and 12% in a study published by Riordan, et al 27 Finally, we note that hemorrhage is an important mortality factor; which was the most common presentation in our sample; occurring in 24 out of 30 pediatric patients, while in adults, it was present in 23 out of 50.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The mortality in the adult population is similar to that reported by Hillman, et al 26 as well as other literature, such as Rinaldi et al 21 who reported 13.46% mortality rate and other studies with a range from 10 to 15%. 17,20 However, the mortality in the pediatric population is vastly different from that of the literature, being 33.3% in our study and 12% in a study published by Riordan, et al 27 Finally, we note that hemorrhage is an important mortality factor; which was the most common presentation in our sample; occurring in 24 out of 30 pediatric patients, while in adults, it was present in 23 out of 50.…”
Section: Discussioncontrasting
confidence: 77%
“…30,31 32 The aforementioned has been highlighted as a poor prognostic factor in both children and adults, without being correctly demonstrated by the literature. [30][31][32][33][34][35][36] In our study we found a IJMS high prevalence of symptom onset in non-laboral hours, but a future and more specific analysis focusing on this exact variable is necessary.…”
Section: Discussionmentioning
confidence: 98%
“…Children harboring a previously undiagnosed intracranial AVM and present with a hemorrhagic ictus, are reported to suffer a 12% chance of sudden death [16]. Subsequent diagnostic imaging workup verified that a posterior fossa AVM was present in 57% of fatal cases, and all of them were associated with malformations located in areas with an associated increased risk of potential herniation, as in our case.…”
Section: Introductionsupporting
confidence: 74%
“…If patients with surgical indications have more serious condition or their secondary cause is found, surgical treatment will be adopted to mainly reduce intracranial pressure, remove hematoma, and save the life of patients. In addition, patients need to control blood pressure to reach the standard and be stable for life [ 16 ]. The prognosis of the disease is often related to the amount of bleeding, bleeding sites, and complications.…”
Section: Discussionmentioning
confidence: 99%